How to choose a craniotomy for the intracranial foreign bodies when the airway was occupied: a case report. Issue 1 (28th March 2021) - Liu, De‐Xing; Wen, Dan; Zhu, Yu‐Hang; Zhang, Fan; Li, Juan
Abstract : Background: Intracranial foreign bodies caused by trauma are rare in clinical emergency cases. Similar reports in the past pay less attention to establish artificial ventilation for these patients for the following anesthesia and surgery. Case information: We reported a 3‐year‐old boy who suffered from oral penetration of the cerebellum from the skull base by a chopstick after a fall. To avoid pediatric tracheotomy, we conducted a reconstruction analysis by spiral CT scan and found a transnasal tracheal intubation pathway allowing the endotracheal tube through, successfully established artificial ventilation, and smoothly implemented the removal surgery of foreign bodies under general anesthesia. The child was cured and discharged without surgical complications or sequelae during the follow‐up. Conclusion: Imaging technology plays an important role in determining airway during endotracheal intubation.